An intelligent magnetic tape controller - McGuffog, Alexander Donald (Department of Electrical Engineering, 2023)
This thesis describes a system to allow a mass storage device to be installed in a position remote from the computer system which controls it. This system is intended to allow undergraduate students in the Electrical Engineering department at UCT to make use of two nine channel tape drives installed in the undergraduate interfaced to accessed by laboratory for project work. The drives are the department's PDP-11/23 computer, and may be standard operating system directives, as the controller simulates a conventional computer peripheral. The system consists of an SA-Bus based tape transport controller which interfaces to the host computer system via a serial line. The following hardware was designed and built specifically for this system : 1. A CPU card based on the in Tel 80188 microprocessor, incorporating high speed DMA (direct memory access) channels and two interrupt driven serial lines. 2. A timing and control module for the tape transports. This consists of two SA-Bus cards. Two sets of software were written for the system. These are the following : 1. Software to operate the tape controller. This consists of six modules written in Pascal-86 and 8086 assemblers. 2. Software to allow the PDP-11/23 to control the tape drives. This is in the. form of an RSX-11 device driver written in PDP-11 assembler. To allow the particular to proposed local system allow area highly modular form. to be easily the system to network) , the upgraded in the future (in be incorporated into UCT's software was written in an addition to being controlled by a host system in remote mode the tape controller also has the ability to perform a variety of operations in local mode. These include the ability to copy and erase tapes, as well as a comprehensive set of diagnostic functions. When in local operations mode the controller is menu driven, making its use by persons who are not familiar with it quick and easy.